Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I've been emptying my notebook over this, and still reach the same nothing at the end.
I'm trying to prove that the following equation is true, with no luck:

$\forall n,k \in \mathbb{N}^+ . k<n\to \binom{n-1}{k-1}\binom{n}{k+1}\binom{n+1}{k}=\binom{n-1}{k}\binom{n}{k-1}\binom{n+1}{k+1}$

share|cite|improve this question
For a combinatorial proof, see this answer. – Mike Spivey Jan 21 '13 at 16:57
up vote 1 down vote accepted



$$=\frac{(n-1)!}{k!(n-1-k)!}\frac{n!}{(k-1)!\{n-(k-1)\}!}\frac{(n+1)!}{(k+1)!\{(n+1)-(k+1)\}!}$$ as $ n-k-1=n-1-k,n+1-k=n-(k-1),n-k=(n+1)-(k+1)$

$$=\binom{n-1}k\binom n{k-1}\binom{n+1}{k+1}$$

We know, $\binom m r=0$ if $r<0$ or if $r>m\implies \binom m r>0$ if $0<r<m$


$\binom{n-1}k>0$ if $0\le k\le n-1$

$\binom n{k-1}>0$ if $0\le k-1\le n\iff 1\le k\le n+1$

$\binom {n+1}{k+1}>0$ if $0\le k+1\le n+1\iff 0\le k\le n$

All the three will be $>0$

if $$\text{max}(0,1,0)\le k\le \text{min}(n-1,n+1,n)\implies 1\le k\le n-1$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.